Effect of cooking duration on carotenoid content, digestion and potential absorption efficiencies among refined semolina and whole wheat pasta products. Issue 11 (19th May 2022) - Oduro-Obeng, Hannah; Apea-Bah, Franklin B.; Wang, Kun; Fu, Bin Xiao; Beta, Trust
Abstract : The bioaccessibility of carotenoids from cereal -based foods is influenced by the food matrix or type, food processing and carotenoid species. Abstract : The bioaccessibility of carotenoids varies among different foods due to factors such as food matrix composition and type or extent of processing. Hence it is important to understand the extent to which these factors influence carotenoid bioaccessibility after the consumption and digestion of food. This study evaluated the carotenoid content, micellization efficiency, digestive stability, antioxidant activity and bioaccessibility of carotenoids as impacted by wheat cultivar and cooking duration among whole wheat flour (WWF) and refined semolina (RS) pasta. WWF and RS pasta were processed from three durum wheat cultivars (AAC Spitfire, CDC Precision, and Transcend) and cooked to al dente (Al), fully cooked (FCT) or overcooked (OC). The study showed that the wheat cultivar and cooking duration were significant functions of bioaccessible lutein in RS samples while only the cultivar influenced the bioaccessibility of zeaxanthin and lutein in WWF samples. In both WWF and RS, the effect of the cultivar on the bioaccessibility of lutein and zeaxanthin was similar and was as follows: Transcend > CDC Precision > AAC Spitfire. Cooking to Al significantly caused an increment in bioaccessible lutein in RS samples regardless of the wheat cultivar. This influence of cooking duration (Al > FCT > OC) was inversely related to the lutein concentrations in undigested pasta (OC = FCT > Al). DPPH scavenging activity among WWF samples was about 2-fold greater or more than that of RS samples regardless of the cultivar or cooking duration before and after digestion. Our data suggest that the effect of wheat cultivar and cooking duration modulates the bioaccessibility and antioxidant activity of RS and WWF pasta products.